Tanggung Jawab Notaris terhadap Keabsahan Perjanjian Pranikah yang Tidak Didaftarkan dan Implikasinya terhadap Aset dalam Perkawinan - Giyo Sastra Manggali (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines notary responsibility and legal protection of assets in prenuptial agreements that are not registered with the competent authority. The main issues discussed are the limits of notary responsibility for the nonregistration of a prenuptial agreement and the legal protection of the parties’ assets when the agreement is only made in the form of an authentic deed but is not administratively recorded. This research uses a normative juridical method with statutory and conceptual approaches. The legal materials used include laws and regulations, Constitutional Court decisions, legal literature and relevant scholarly journals. The results show that a notary is responsible for the formal validity of the deed, compliance with deed-making procedures, reading of the deed, safekeeping of the deed minuta, issuance of copies and legal counseling to the parties. However, a notary is not automatically responsible for registering the prenuptial agreement, unless there is a specific power of attorney granted by the parties. An unregistered prenuptial agreement remains legally binding in the internal relationship between husband and wife, but it does not have optimal legal effect against third parties because it does not fulfill the principle of publicity. Consequently, legal protection of assets becomes limited, particularly in relation to creditors, financial institutions, heirs and other interested third parties. In mixed marriages between Indonesian citizens and foreign nationals, registration of a prenuptial agreement becomes even more important because it relates to the protection of Indonesian citizens’ assets, especially land rights that are restricted under national agrarian law.